Pengaruh Sonikasi Terhadap Sifat Fisik Formula Herbisida yang Ditambahkan Surfaktan Dietanolamida - Rusdiana, Ika Agustin; Hambali, Erliza; Rahayuningsih, Mulyorini (AGRORADIX : Jurnal Ilmu Pertanian, 2018)
Diethanolamide is a non-ionic surfactant from palm oil derivatives that can replace the use of polyoxyetilenamine surfactant in a commercial herbicides. But there is a weakness in the formula it has low visual appearance to the consumer industry. The aim of this research was to study the improvement of herbicide characterization through sonication method. This study was designed using a complete randomized design of 2 factors with factor 1 is the time of sonication (0, 30, 60, 90 minutes) and factor 2 is amplitude (20%, 30%, 40%).The best herbicide formula after sonication at 40% amplitude, 90 minute sonication time having a surface tension of 23,42 dyne/cm, contact angle of 0o and turbidity of 98 NTU.